Evidence-based research project In support of the President's 8-point agenda - Philippines. Congress (1987-). House of Representatives; Ateneo De Manila University ([Quezon City, Philippines] [The House of Representatives and Ateneo De Manila University], 2024)
This collection of Policy Briefs is based on the research studies carried out under the “Evidence-based Research in Support of the President’s 8-Point Agenda” project, with funding from the House of Representatives, and implemented by the Ateneo Center for Economic Research and Development of Ateneo de Manila University.
Electricity: Spikes in Power Prices: Unravelling Grid Congestion and Disruptions in the Philippines / Majah-Leah V. Ravago, Michael R.M. Abrigo, Patrizia S. Benedicto, Natasha Brigitte M. Kuan, J. Kathleen P. Magadia, Charlotte Marjorie L. Relos – Food: Rice production, rice prices, and the rice tarrification law / Marites M. Tiongco, Albert Lamberte, Karlo Fermin S. Adriano, Eva Marie D. Aragones, Emmanuel D.C. Barnedo – Health: Strengthening Primary care financing in the Philippines / Valerie Gilbert Ulep, Miharu Jay Kimwell, Romelei Camiling-Alfonso, Denese de Guzman, Arianna Maever L. Amit, and Ida Marie Pantig – What ails Philippine education?: Insights from the 2022 PISA assessments / Leonardo Lanzona, Jr., Geoffrey Ducanes, Loriel Eleazar, and Katheryn Hidalgo – Fiscal management: Enhancing growth, managing populations, and fiscal policy / Lawrence B. Dacuycuy – Monetary and financial stability: Monetary and financial agenda towards inclusion, consumer protection, and innovation / Luis F. Dumlao, Alvin P. Ang, Ser Percival K. Pena-Reyes, Genesis Kelly S. Lontoc, and Satyabhama Andrea C. Gulapa – Jobs and Connectivity: Rationalizing infrastructure investments: The impact of improved inter-island transport connectivity on local employment / Kris Francisco and Neil Irwin Moreno – Outlook and Policy Options for Philippine Employment toward 2040 / Philip Arnold P. Tuano, Joselito T. Sescon, Prezatia Moseska Maria T. Vicario, Rolly Czar Joseph T. Castillo, Cymon Kayle Lubangco, and Brian Jason H. Ponce – Research, development, and digital economy: Productivity-enhancing research and development: Public spending and institutions / Karl Robert Jandoc, Benjamin Radoc, Jr., Ludigil Garces, Mae Hyancinth Kiocho, and John Faust Turla – Blue and green economy: Addressing environmental challenges and impacts of climate change Policy interventions for safe and healthier communities / Jefferson Arapoc, Charina Lyn Amedo-Repollo, Asa Jose Sajise, and Allyssa Marie Mercado – Government Rightsizing, Bureaucratic Efficiency, and E-governance: Improving Public Service Delivery through effective public sector rightsizing / Ronald U. Mendoza, Alex B. Brillantes, Jr., Ainna Shariz Comia, Miguel Paje, and Karl Emmanuel Ruiz – Peace and security: Defending the West Philippine Sea: Achieving genuine national security against a backdrop of global shifts in power and persistent domestic security challenges / Herman Joseph S. Kraft, Robin Michael Garcia, Ronna Shane M. Belaro, Paula Patrice Hamoy, and Rodel Cabrido.
Keywords: Philippines -- Politics and government -- 1986-.; Philippines -- Economic policy -- Case studies; Philippines -- Social policy -- Case studies